Perancangan Alat Penyortir Telur Ayam Berbasis Arduino Menggunakan Sensor Ldr (Light Dependent Resistor) Dan Sensor Berat (Load Cell) - Egantara Satria Utama; Poerbaningtyas E (J-INTECH ( Journal of Information and Technology), 2022)
Seeing the conditions where the need for consumption of chicken eggs continues to increase, it is necessary to pay attention to the quality of eggs that are suitable for consumption. However, currently the method for the process of sorting the quality of broiler eggs that is massively used is using manual methods such as utilizing sunlight or putting them in water. Based on these problems, the idea came up to make a chicken egg quality sorter using a weight sensor (Load Cell) and an LDR (Light Dependent Resistor) sensor. Based on the tests that have been carried out, the use of these two sensors is able to speed up and simplify the process of sorting eggs with precise results, where the use of a Load Cell sensor is more accurate in measuring egg weight and an LDR sensor that can read the intensity of light that penetrates the eggs from the HPL LED which determine egg quality. that was built and the application that has been made. That has been made can operate properly and provide benefits for the surrounding community, namely wifi access at an affordable cost.